Synchronization of chaotic-type delayed neural networks and its application - Kalpana, Muthusamy; Ratnavelu, Kurunathan; Balasubramaniam, Pagavathi; Kamali, Mohd Zahurin Mohamed (Springer Verlag, 2018)
Our proposed image encryption is based on synchronization of chaotic fuzzy cellular neural networks (FCNNs) with different time delays and uses sampled-data controller. (i) It is known that the chaotic system plays a vital role in secure communication. (ii) FCNNs are more suitable for image processing due to its local connectedness. (iii) There are some results derived on theory part for the problem of synchronization of chaotic delayed FCNNs. (iv) We raise the following question: Is it possible to utilize these obtained chaotic values via FCNNs to image encryption? (v) Finally, we tried the above and succeed. Moreover, numerical instance and comparison results show that the proposed scheme works well and is resistant to differential attack.